Risk and coping mechanisms of the carp spawn fishing community of the Halda river, Bangladesh - Akhtar, Aysha; Islam, Md Tarikul; Islam, Md Shafiqul; Mia, Muhammad Moznu; Bhuyan, Md Simul; Kibria, Md Manzoorul; Muhammad Sharif, Abu Sayeed; Kamal, Abu Hena Mustafa (Bangladesh Journal of Zoology, 2017)
To assess the livelihood risks and coping mechanisms of the spawn fishing community of the Halda river, Chittagong, Bangladesh was conducted. Four areas, namely Ankurighona, Gorduara, Madarimukh and Madunaghat were selected on the basis of the aggregation of spawn fishers. A structured questionnaire survey was made on 152 spawn fishers in two categories i.e. boat owner and hired laborers to collect primary data. Three major man-made risks, namely catch of brood fish, non-functioning sluice gates and cutting of river bends related to egg collection were mentioned by the spawn fishers while salinity intrusion, river erosion and fluctuation in weather variables were found as the main natural risks. Willingness to continue egg collection despite the risks was disagreed by most of the respondents while those who were found to continue egg collection mentioned their driving forces as high profit, tradition and hobby. The respondents expressed that they cannot take any measures to mitigate the risks of salinity intrusion, weather fluctuation, mortality of spawn, non-functioning sluice gates, cutting of river bends and political influences. However, informing police and raising awareness to stop illegal catch of brood, construction of proper sluice gates, stop further cutting of river bends and rehabilitation of erosion victims were mentioned as probable solutions. Bangladesh J. Zool. 45(1): 85-96, 2017